Mitigation in Chinese online consumer reviews. (December 2018) - Ren, Wei
Highlights: The paper investigated mitigation in Chinese online consumer reviews. Mitigation was also examined against positive/negative nature of the comments. The study shed light on cross-cultural differences in online consumer reviews. A hearer-speaker dichotomy cannot explain reviewers' motivation to mitigate. Abstract: With the increasing popularity of online shopping among consumers and the continuous development of interactive digital communication, online reviews are prevalent in contemporary life. As a new genre, online reviews deserve more attention in language and discourse studies. Existing studies in this field predominantly investigate online reviews in English. More research on a greater variety of languages is needed to better understand the linguistic features of this genre and the localization of the social practice. In addition, how consumers mitigate their evaluations lacks systemic exploration. This study provides an analysis of mitigation strategies in Chinese consumer reviews, based on a dataset of user-generated online comments on Kindle E-Reader collected from Amazon China. The study examines the usage and frequency of different types of mitigation devices in the reviews. The distribution of mitigation is further investigated against the positive or negative nature of the comments. Since Chinese is a logographical language, exploring Chinese mitigation identified some particular usages. The study demonstrates that the investigation into mitigation in Chinese online consumer reviews could provide insights into cross-cultural differences in this genre.